MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE SEPAK BOLA VERBAL - I Ketut Alit Adri Adnyana; A. A Sujadi (Universitas Sarjanawiyata Tamansiswa, 2015)
The research purposes to increases and mathematics achievement with Verbal Football method in class VII A SMP Negeri 2 Sanden Bantul. The research subjects were students of class VII A SMP Negeri 2 Sanden and object of this research were interests and mathematics achievement. The results showed that interest and mathematics achievement increase. The results can be seen from questionnaire data pre-term by 72.79% with moderate category, increased to 76.89% with the high category in first term. Then increased again to 82.42% in second term with the very high category. The results of mathematics achievement obtained from test, with percentage completeness obtained pre-term 61.29% with an average of 69.51. In first term increased to 80.65% with an average of 78.87 and in second term increased to 100% with average value of 91.45.